Exogenous lipid pneumonia related to long-term use of Vicks VapoRub® by an adult patient: a case report. Issue 1 (January 2016) - Cherrez Ojeda, I.; Calderon, J.; Guevara, J.; Cabrera, D.; Calero, E.; Cherrez, A.
Abstract Background Use of petroleum-based over the counter remedies such as Vicks VapoRub to alleviate symptoms of rhinitis is common and can be effective, but carries under-appreciated risks of adverse side effects. In this case report we highlight Exogenous Lipoid Pneumonia (ELP), an uncommon condition that results from accumulation of exogenous lipids in the alveoli, as an adverse side effect of long-term Vicks VapoRub use. Case presentation We present the case of an 85-year-old female patient with ELP apparently due to continuous application of Vicks VapoRub® to her nostrils to alleviate chronic rhinitis. She was diagnosed incidentally via chest radiograph and computed tomography (CT) scan done as follow up to finding elevated C-reactive Protein during a routine exam. The CT scan revealed a pulmonary consolidation in the lower lobe of the right lung with fat density combined with low density areas associated with focal ground-glass opacities. The patient was advised to discontinue use of petroleum-based products, and was prescribed intranasal corticosteroids for her rhinitis. Follow up 2 years later showed that the lipid consolidation had diminished in size by approximately 10 %. Conclusion Physicians must be aware that ELP can develop as a result of long-term application of petroleum-based oils and ointments to the nose and discourage such use of these products. Patients who have used petroleum-based products in this way should be screened for ELP. CT scan is the best imaging modality for establishing the diagnosis. The treatment of this condition is not well defined, but, as shown in this case, the size of the lipid mass can decrease after use of petroleum based substances is discontinued.